About housing: PB questionnaire - Bokov, Andrey; Gnedovsky, Sergey; Oreshkin, Sergey; Filippov, Valery (project baikal, 2026)
The article includes the results of a survey conducted among several architects combining theoretical fundamentals with rich practical experience. The respondents were asked a number of open-ended questions related to the current state and development prospects of housing construction in Russia and around the world. The main topic of the conversation was the ratio between multi-storey and multi-apartment housing construction and the of low- and medium-rise housing, including individual one.